Financial Performance Efficiency: Determinants of Return on Invested Capital - Widiyanti, Retno; Sumarna, Alfonsa Dian (Politeknik Negeri Batam, 2025)
With the growth of the capital market in Indonesia, stocks are an attractive investment option. The healthcare sector plays a strategic role in supporting public health services, which makes it much sought after by investors. Inconsistency results from the fact that much previous research has created a knowledge gap in this field. This study aims to determine the effect of capital structure on the efficiency of financial performance partially and simultaneously in healthcare sector companies from 2019 to 2021. Based on the Eviews statistical analysis and testing results, the partial Self-Financing Ratio, Long-Term Asset Ratio, and Financial Leverage Ratio have an insignificant effect on financial performance efficiency. The Fixed Asset Ratio variable partially and significantly affects financial performance efficiency. The test results simultaneously show that the variables Self-Financing Ratio, Long-Term Asset Ratio, Financial Leverage Ratio, and Fixed Asset Ratio significantly affect financial performance efficiency. Novelty in this research is using the capital structure, which is proxied by the Self-financing Ratio (SFR), Long-term Asset Ratio (LAR), Financial Leverage Ratio (FLR), and Fixed Asset Ratio (FAR) across different company sectors and periods of panel data. The implication from this analysis of these ratios and industry benchmarks can provide a more comprehensive picture of a company’s financial health and ability to generate sustainable returns on its invested capital.